Duplex DNA engagement and RPA oppositely regulate the DNA-unwinding rate of CMG helicase - Hazal B. Kose (Nature Portfolio, 2020)
During eukaryotic chromosome replication cells utilize ring-shaped CMG helicase that separates the two strands of the DNA double helix. Here the authors reveal that CMG helicase activity is inhibited by duplex DNA engagement at the fork, which is relieved by binding of RPA to the lagging-strand template.